Growth, Structure and Prediction of the Thermal Internal Boundary Layer - Comrie, Andrew Charles (Department of Environmental and Geographical Science, 2014)
The Thermal internal Boundary Layer (TIBL) is a dynamic and turbulent mesoscale feature of the coastal atmosphere that forms over the land during conditions of onshore flow. The TIBL develops as an adjustment of the atmospheric boundary layer to the discontinuities of temperature and roughness that occur at the interface between the underlying marine and terrestrial surfaces. The resulting formation of a characteristically convex mixed layer below relatively stable air aloft has serious implications for the dispersion of pollutants in shoreline environments. Although a wide range of research relating to various features of the TIBL may be found in the literature, relatively few broadly-based studies have been performed. This study has employed both airborne and surface measurements to obtain a comprehensive spatial and temporal data set, in order to elucidate aspects of the characteristic structure and behaviour of the TIBL. TIBL growth was found to follow a diurnal pattern, the initially irregular boundary becoming more uniform during the day as a steady balance between various factors was achieved. The TIBL was associated with a layer of uniform wind speed anti direction flowing perpendicular to the coastline, within which warmer temperatures and changes in relative humidity and moisture content were observed. The temperature structure of the onshore flow strongly influenced the intensity of turbulence encountered in the TIBL and the degree of entrainment aloft. Patterns of turbulent properties displayed significant increases in the TIBL, which were relatively abrupt near the surface and more gradual towards the top of the TIBL. Measurements of sensible heat flux revealed strong undulations in TIBL structure due to transitory eddies and thermal upcurrents. Certain theoretically based predictive equations of TIBL height displayed the best overall performance out of eight selected models, and some promise was shown by an empirical formulation. TIBL development was generally complex and irregular within the first few kilometres of the shore, while further inland more regular TIBL formation enabled the relatively accurate observation and prediction of TIBL height.